Efeito do bloqueio de receptores de mineralocorticoide nas alterações vasculares induzidas pela ovariectomia em vasos de condutância e resistência de ratas - Marcarini, Wena Dantas (2017)
Cardiovascular diseases are one of the major causes of morbidity and mortality in postmenopausal women who lack the cardioprotective role of estrogen. Estrogen deficiency is related to endothelial dysfunction and increased oxidative stress. At the same time, studies show that the blockade of MR receptors reduces the oxidative stress present in some cardiovascular diseases, in an animal model. Thus the objective of this study was to evaluate the effect of MR receptor blockade on the vascular function of conductance and resistance arteries isolated from ovariectomized rats, focusing on NO bioavailability and oxidative stress. Thus, the animals were separated into 4 experimental groups: Sham and Ovx, treated with vehicle carboxymethylcellulose (0.5% administered 0.3 ml via gavage); Sham Spiro and Ovx Spiro, treated with spironolactone (80 mg / kg dissolved in carboxymethylcellulose, via gavage). All treatment protocols were maintained for 8 weeks. Blood pressure measurements were performed in anesthetized animals and vascular function was investigated through in vitro vascular reactivity studies in segments of the aorta and third branch of the mesenteric artery. At the end of the treatment, we verified that there was no alteration of the blood pressure in ovx rats when compared to the sham group, and the treatment with spironolactone did not modify this parameter. As for reactivity, the treatment reduced the contractile response to phenylephrine in aortic rings, improved acetylcholine-induced relaxation and did not affect relaxation to sodium nitroprusside. However, in mesenteric arteries none of these parameters were altered when compared to ovx and sham rats, both in the absence or presence of spironolactone treatment. Removal of the endothelium and preincubation with L-NAME (100 μM) shifted the concentration-response curve to phenylephrine to the left, however, this response was of greater magnitude in the aorta of sham rats when compared to ovx. MR blocker treatment equaled the concentration-response curve to aorta phenylephrine isolated from ovx rats with those obtained from sham rats, suggesting an improvement in NO bioavailability in estrogen deficient rats. In mesenteric arteries, no difference was found in the concentration-response curves to phenylephrine, between ovx and sham rats, in the presence or absence of MR blocker. Incubation with thiram (1 mM) promoted reduction of the response to phenylephrine that was higher in the aorta of ovx rats, suggesting greater release of reactive oxygen species. Incubation with apocynin (30 μM) and catalase (1000 U ∙ mL-1) reduced the concomitant response to phenylephrine only in the aorta isolated from ovx rats. Treatment with MR blocker did not modify the concentration-response curve to phenylephrine in the presence of thyroxine, apocynin and catalase in aorta isolated from ovine rats, suggesting a reduction of oxidative stress in estrogen deficient rats. In mesenteric rings, tiron, apocynin and catalase did not alter vascular reactivity in either group. Indomethacin (10 μM) significantly reduced the contractile response to phenylephrine in the aorta of both groups. However, the magnitude of this effect was higher in the isolated aorta of ovx rats suggesting greater release of constrictor prostanoids. Treatment with MR blocker, however, abolished these effects. In mesenteric the maximal response to phenylephrine was reduced in the sham group after incubation with indomethacin, which was restored after treatment with spironolactone. As for the ovx group, there was no change in the contractile response. Treatment with spironolactone reduced the basal production of superoxide anion in the aorta and promoted reduction of vascular protein expression of gp91phox, NOX4 and SOD, as well as reduction of plasma levels of malondialdehyde in sham and ovx rats. In conclusion, our results suggest that the reduction of estrogen levels with consequent increase of ROS and reduction of the bioavailability of NO in the aorta act together to produce the vascular alterations, which are reversed after treatment with MR blocker